Neoadjuvant chemoradiotherapy for locally advanced pancreas cancer rarely leads to radiological evidence of tumour regression. Issue 9 (2nd December 2012) - Dudeja, Vikas; Greeno, Edward W.; Walker, Sidney P.; Jensen, Eric H.
Abstract Background Neo‐adjuvant chemo‐radiotherapy has been proposed to improve resectability of locally‐advanced pancreatic cancer (LAPC). However, the ability of neo‐adjuvant therapy to induce radiological tumour regression has not been reported. Methods Pre‐ and post‐treatment computed tomography (CT) scans of patients undergoing neo‐adjuvant chemo‐radiotherapy for LAPC were reviewed. LAPC was sub‐classified into borderline resectable disease [≤180° involvement of the superior mesenteric artery (SMA); short‐segment encasement/abutment of the common hepatic artery; or tumour‐associated deformity, abutment or short‐segment occlusion of the superior mesenteric vein (SMV)/ portal vein (PV) that was amenable to vascular resection and reconstruction] and locally advanced un‐resectable pancreatic cancer (vascular involvement more than that described for borderline resectable pancreatic cancer). The radiological response and surgical resection rates were assessed. Results Sixteen patients received neo‐adjuvant therapy for LAPC during 2005–2008. Regression of major vascular involvement, i.e. un‐encasement or regression of abutment of any involved vessels was not observed in any patient. Pre‐ and post‐treatment tumour densities were not statistically different. Fifty per cent of patients with borderline resectable disease and none of the patients with locally advanced un‐resectable pancreatic cancer eventually underwent surgical resection. Conclusion Neo‐adjuvant treatment does not induce radiological tumour regression of LAPC with major vascular involvement. Patient selection for neo‐adjuvant trial enrolment should remain focused on borderline disease which may have a potential for surgical resection.